Aristotle’s lobster: the image in the text ... - Fürst Von Lieven, Alexander; Humar, Marcel; Scholtz, Gerhard (Humboldt-Universität zu Berlin, 2020)
The Anatomai, a lost work written by Aristotle, must have contained a collection of various drawings and figures of species as well as their organs. In his texts (mainly the Historia animalium), Aristotle is often referring to the drawings after the description of species. Our study applies the method of the comparative view (‘Vergleichendes Sehen’) to provide an access to and reconstruction of Aristotle’s lost illustrations based on his textual descriptions. As an example, we chose the treatment of the European lobster (Homarus gammarus L., 1758) in the Aristotelian corpus as a case study. First, we analyse the etymology of the Greek term astakós referring to the lobster and provide an overview on the putative synonyms. Second, we confront the textual basis of the description with several questions concerning the degree of abstraction, the relation between text and image, and the spatial orientation of the image. Finally, we present a step-by-step reconstruction of Aristotle’s illustrations of the lobster ...